(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Artificial Intelligence (AI) is revolutionizing various sectors, including e-commerce, with its transformative potential. Despite being in its early stages of development, AI is reshaping business operations, albeit primarily adopted by large corporations due to its complexity and infrastructure requirements, resulting in limited public awareness of its applications in e-commerce. By synthesizing research conducted across various disciplines such as e-commerce, marketing, information systems, and management, the study endeavours to narrow the divide among technological advancements and practical applications in e-commerce. Findings underscore the prevalent utilization of AI subsets such as chatbots, voice assistants, personalization, recommendation systems, and automation in e-commerce, with projections indicating significant growth potential as AI technology evolves. Moreover, the study emphasizes the importance of exploring the practical implications of AI in e-commerce to gain a comprehensive understanding of its functionality